Глобальний атрактор для автономного хвильового рівняння в Rn з неперервною нелінійністю - Станжицький, О.М.; Горбань, Н.В. (Український математичний журнал, 2008)
Исследована динамика решений автономного волнового уравнения в Rn с непрерывной нелинейностью. Получены априорные оценки. Для m-полупотока обосновано существование инвариантного глобального аттрактора. We consider the dynamics of solutions of autonomous wave equation in Rn with continuous nonlinearity. The a priori estimates are obtained. The existence of compact invariant global attractor for m-semiflow is justified.